The Gender Regime of Anti-Liberal Hungary - Fodor, Eva (Springer International Publishing : Imprint: Palgrave Pivot, 2022)
This authoritative analysis of anti-liberal Hungary's 21st century twist on "Kinder, Küche, Kirche" exposes its exploitation of women not only as unpaid carers in the home but also as a source of cheap paid labor. Fodor deftly links the Orbán regime's notorious opposition to gender equality to its embrace of pronatalism, xenophobia, and expanded funding for church-based childcare and eldercare. A terrifying, essential read. -Ruth Milkman, City University of New York Graduate Center and author of On Gender, Labor, and Inequality (lllinois, 2016) and Immigrant Labor and the New Precariat (Polity 2020) Finally, a book that offers brilliant insight into the seemingly perplexing: the gender politics of the contemporary Hungarian state. With sharpness and wit, Fodor reveals how the public attack on gender--indeed, even on the concept of gender itself--goes hand-in-hand with the rise of authoritarian rule and right-wing populism. Giving this newgender regime a name, "the carefare state," Fodor uncovers how it became so foundational to anti-liberal currents in Hungary. Part history of the present and part social policy analysis, The Gender Regime of Anti-Liberal Hungary makes an enormous contribution to understandings of anti-democratic politics, gender relations, and social inequality in Hungary and beyond. -Lynne Haney, Professor of Sociology, New York University, USA This open access book explains the new type of political order that emerged in Hungary in 2010: a form of authoritarian capitalism with an anti-liberal political and social agenda. Eva Fodor analyzes an important part of this agenda that directly targets gender relations through a set of policies, political practice and discourse-what she calls "carefare." This book reveals how carefare is the anti-liberal response to the crisis-of-care problem and establishes how a state carefare regime includes selective pronatalist measures along with the familialization and sentimentalization of care, with the purpose of disciplining women into doing an increasing amount paid and unpaid work without fair remuneration. Fodor analyzes elements of the carefare regime in depth and contrasts it to other social policy ideal-types, demonstrating how carefare is not only a set of policies targeting women, but an integral element of anti-liberal rule that can be seen emerging globally. Eva Fodor is Professor of Gender Studies and Co-Director of the Democracy Institute at the Central European University located in Budapest, Hungary and Vienna, Austria. Her research focuses on gender inequalities in the labor market and social citizenship rights from a comparative perspective.